Engineering and Application of Fe-TiO2/MOR Zeolite Photocatalysts for the Photodegradation of Methylene Blue Dye Waste - Sholikah, Liqanatul Putri; Sumari, Sumari; Permatasari, Suryani Indah (KOVALEN: Jurnal Riset Kimia, 2025)
The use of dyes such as methylene blue is widespread. However, if methylene blue is discharged without prior treatment, it can lead to pollution problems. In this study, the engineering of zeolites and the degradation mechanism of methylene blue using Fe-TiO2/MOR zeolite as a photocatalyst were investigated. XRD characterization results revealed that Fe-TiO2/MOR zeolite has a crystalline phase. Based on XRF characterization, the percentage of Fe and Ti significantly increased, indicating the successful immobilization of TiO2 and doping of Fe3+ into the zeolite structure to form a composite. The morphological analysis of the Fe-TiO2/MOR zeolite composite showed a rough surface, which could affect its surface area. The Fe-TiO2/MOR zeolite photocatalyst has a band gap of 3.08 eV, allowing it to absorb visible light more efficiently. The study on the application of methylene blue photodegradation using Fe-TiO2/MOR zeolite as a photocatalyst demonstrated higher degradation efficiency compared to using inactivated, non-immobilized, and undoped mordenite zeolite. With an optimal mass of 0.03 grams, a contact time of 90 minutes, and a pH of 10, the percentage of degraded methylene blue reached 98.91%. The Fe-TiO2/MOR zeolite composite has the potential to be used as a photocatalyst in methylene blue photodegradation reactions.